Analisis Yuridis Perlindungan Pelaku Usaha Agroindustri Pengelolaan Kakao di Indonesia - Gyska Indah Harya (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The cocoa agroindustry plays a strategic role in the national economy; however, business actors, particularly MSMEs, face structural constraints such as limited access to finance, technology and bargaining power. This study aims to analyze juridically the regulatory framework and the effectiveness of legal protection for cocoa processing businesses in Indonesia using a normative legal approach. The findings show that regulatory instruments exist, but their implementation remains suboptimal due to weak policy coordination, market inequality and limited institutional capacity. This study proposes a legal protection model based on justice and legal certainty principles to support cocoa industry downstreaming.